EXPLORING THE EFFECTIVENESS OF ICT TOOLS FOR ONLINE TEACHING, LEARNING AND ASSESSMENT AMONG PRE-SERVICE TEACHERS FROM A GHANAIAN UNIVERSITY - Paul Kwame Butakor, (International Journal of Innovative Technologies in Social Science, 2024)
As a result of the COVID-19 pandemic, universities in Ghana have embraced the use of Information and Communication Technology (ICT) tools for online teaching, learning, and assessment. However, despite the increasing integration of these tools in education, there is a need to explore their effectiveness in enhancing students learning and educational outcomes. The purpose of this study was thus to explores the effectiveness of integrating ICT tools for online teaching, learning, and assessment in one of the Universities in Ghana. To achieve the purpose of this study, the quantitative descriptive survey design was adopted where a convenient sample of 301 pre-service teachers were selected through and surveyed. The data collected were analyzed using SPSS version 25 and the results showed that majority of pre-service teachers perceived ICT tools as positive for online teaching, learning and assessment. However, challenges like technical skills, unreliable internet, limited access, training needs, academic integrity, support, and student engagement were highlighted as detrimental to online teaching, learning and assessment. The results further revealed interesting age differences in pre-service teachers’ viewpoints about effectiveness of ICT tools with older students perceiving ICT tools as more effective for online teaching and learning but less so for online assessment. It was thus recommended that there should be increased educator support and training on ICT integration in teaching and learning, promoting online student collaboration, soliciting ongoing student feedback, and targeted training on effective use of technology for learning for mature learners.